The structural, functional, and dynamic effect of Tau tubulin kinase1 upon a mutation: A neuro‐degenerative hotspot - Ahamad, Shahzaib; Hema, Kanipakam; Kumar, Vijay; Gupta, Dinesh (Journal of cellular biochemistry, 2021)
Alzheimer's disease (AD) is a progressive disorder that causes brain cells to degenerate and die. AD is one of the common causes of dementia that leads to a decline in thinking, behavioral and social skills that disrupts a person's ability to function independently. Tau‐tubulin kinase1 (TTBK1) is a crucial disease regulating AD protein, which is majorly responsible for the phosphorylation and accumulation of tau protein at specific Serine/Threonine residues found in paired helical filaments, suggesting its role in tauopathy. TTBK1 involvement in many diseases and the restricted expression of TTBK1 to the central nervous system (CNS) makes TTBK1 an attractive therapeutic target for tauopathies. The genetic variations in TTBK1 are primarily involved in the TTBK1 pathogenesis. This study highlighted the destabilizing, damaging and deleterious effect of the mutation R142Q on TTBK1 structure through computational predictions and molecular dynamics simulations. The protein deviation, fluctuations, conformational dynamics, solvent accessibility, hydrogen bonding, and the residue‐residue mapping confirmed the mutant effect to cause structural aberrations, suggesting overall destabilization due to the protein mutation. The presence of well‐defined free energy minima was observed in TTBK1‐wild type, as opposed to that in the R142Q mutant, reflecting structural deterioration. The overall findings from the study reveal that the presence of R142Q mutation on TTBK1 is responsible for the structural instability, leading to disruption of its biological functions. The mutation could be used as future diagnostic markers in treating AD. Graphical The structural, functional, and dynamic effect of Tau Tubulin Kinase1 upon R142Q mutation: A neuro‐degenerative hotspot.